2021
DOI: 10.20471/lo.2021.49.01.01
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 and colorectal cancer – signs of a toxic relationship and how to break the cycle: a single institution, tertiary centre experience

Abstract: Colorectal cancer (CRC) is one of the most prevalent oncological diseases globally, taking 3 rd place in incidence in the general population. High in mortality, it is also a form of cancer whose outcome is highly dependable on its stage at diagnosis. therefore, many countries have adopted a more or less successful screening process to ensure early diagnosis and, in turn, higher survival rates and better results overall. The COVID-19 pandemic has altered the established medical routines worldwide, with massivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Five case-series studies, conducted at an institutional level, compared the number of colorectal cancer procedures performed during the pandemic to that performed during preceding years, pre-COVID-19; one of the studies was from an UMIC (China) and four were from HICs (Italy, Romania, Croatia) [ 39 , 57 , 68 , 70 , 75 ]. The relative percentage reduction in the institutional volume of elective colorectal procedures performed ranged from 11.08%–57.3% across these studies [ 39 , 57 , 68 , 70 , 75 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Five case-series studies, conducted at an institutional level, compared the number of colorectal cancer procedures performed during the pandemic to that performed during preceding years, pre-COVID-19; one of the studies was from an UMIC (China) and four were from HICs (Italy, Romania, Croatia) [ 39 , 57 , 68 , 70 , 75 ]. The relative percentage reduction in the institutional volume of elective colorectal procedures performed ranged from 11.08%–57.3% across these studies [ 39 , 57 , 68 , 70 , 75 ].…”
Section: Resultsmentioning
confidence: 99%
“…Eleven of the 18 studies that reported on elective surgery activity were undertaken at an institutional level, which limited their statistical power to show a difference [5,26,39,57,[68][69][70][71][72][73]75]. Case performance reductions were not caused solely by elective surgery service suspensions; ancillary pandemic-or patient-specific determinants are tabulated (Table 5).…”
Section: Backlogsmentioning
confidence: 99%
“…the peak incidence is around and after the age of sixty. in croatia, over 3,500 patients are diagnosed annually, and over 2,100 people die from the disease, making colon cancer the second most often malignant cause of death in the population of croatia (1,3). the national program for early Detection of colon cancer has been implemented in croatia since 2007 by the Ministry of Health in cooperation with regional public health institutes and qualified endoscopists.…”
Section: Introductionmentioning
confidence: 99%